ESG lending - Kim, Sehoon; Kumar, Nitish; Lee, Jongsub; Oh, Junho (Journal of Financial Economics, 2025)
Firms increasingly borrow via sustainability-linked loans (SLLs), contractually tying spreads to their ESG performance. SLLs vary widely in transparency of disclosure regarding sustainability-related contract details and tend to be issued to borrowers with superior ESG profiles. While high-transparency SLL borrowers maintain this performance, low-transparency SLL borrowers exhibit significantly deteriorating ESG performance after issuance. Both high- and low-transparency borrowers pay substantial fees to obtain SLLs. The results are consistent with high-transparency borrowers using SLLs to “certify” their preexisting ESG commitments, but low-transparency borrowers “greenwashing” with empty SLL labels. Evidence on drawdowns, renegotiations, and stock market reactions further supports these interpretations.